Highly efficient nucleic acid encapsulation method for targeted gene therapy using antibody conjugation system - Seokbong Hong; Seung-hwan Jeong; Jang Hee Han; Hyeong Dong Yuk; Chang Wook Jeong; Ja Hyeon Ku; Cheol Kwak (Elsevier, 2024)
Gene therapy has surfaced as a promising avenue for treating cancers, offering the advantage of deliberate adjustment of targeted genes. Nonetheless, the swift degradation of nucleic acids in the bloodstream necessitates an effective and secure delivery system. The widespread utilization of poly(lactic-co-glycolic acid) (PLGA) nanoparticles as drug delivery systems has highlighted challenges in controlling particle size and release properties. Moreover, the encapsulation of nucleic acids exacerbates these difficulties due to the negatively charged surface of PLGA nanoparticles. In this study, we aimed to improve the encapsulation efficiency of nucleic acids by employing negatively charged microbeads and optimizing the timing of the specific formulation steps. Furthermore, by conjugating PSMA-617, a ligand for the prostate-specific membrane antigen (PSMA), with PLGA nanoparticles, we assessed the antitumor effects and the efficacy of a nucleic acid delivery system on a prostate cancer model. The employed technique within the nucleic acid encapsulation system represents a novel approach that could be adapted to encapsulate various kinds of nucleic acids. Moreover, it enables the attachment of targeting moieties to different cell membrane proteins, thereby unveiling new prospects for precise therapeutics in cancer therapy.